The feminist perspective as a counterpoint in the architecture of Anna Bofill (1977–1996) - Gutiérrez-Mozo, María-Elia; Gilsanz-Díaz, Ana; Díaz-García, Asunción; Parra-Martínez, José (Frontiers in Sustainable Cities, 2024)
The vast and plural production of the woman architect, musician, activist, occasional educator and tireless researcher Anna Bofill Levi (Barcelona, 1944) is characterized by certain features that make its author a unique personality, although one hardly known and recognized in the Spanish and international circles that are the custodians of prestige in architecture. She has achieved most public recognition as a composer, the field in which she has been most productive over time and developed the furthest. Her music is characterized by the number of references, especially contemporary, she includes, the wide diversity of countries where it has been performed, and the range of people to whom she has dedicated her works, all these aspects testifying to her cosmopolitan and libertarian spirit and her commitment to equality. Her incessant writing, with all the reading it entails, has also left us with a large body of written work, extending over a number of fields, including most notably her reflections on the influence of the gender-based perspective on urban planning. A factor also reflected in her architecture, for example, in the implementation of participatory processes in her project designs. She joined the Taller de Arquitectura from the time she began her studies at the School of Architecture in Barcelona in 1964—she graduated in 1972—, and then commenced her independent career in 1981, although her first solo works date from 1977. Her work at the head of her office for almost 20 years is evidence of a tireless capacity for work and an unwavering commitment to people's welfare. This paper analyses Anna Bofill's contributions to feminist thinking through her work as an architect. Also, it addresses the study of a cultured person, a woman with great sensitivity and a strong political and personal commitment who has suffered discrimination and who has made rigor and determination the means to achieve her non-negotiable freedom.